Tongkat Pintar ESP32 dengan Deteksi Hambatan Multiarah dan Audio-Haptik Adaptif bagi Tunanetra - Gilang Permana; Reza Rahmadian; Aditya Chandra Hermawan; Mahendra Wisyartono; Ayusta Lukita Wardani (Elposys: Jurnal Sistem Kelistrikan, 2026)
Mobility is a major challenge faced by people with visual impairments in their daily activities. Conventional white canes commonly used still have limitations in detecting obstacles, especially those above ground level and uneven road surfaces. This study aims to develop an ESP32-based smart cane capable of detecting obstacles and road surface conditions while providing effective warnings to users. The system employs multiple ultrasonic sensors positioned at the front, left, right, and bottom of the cane. Sensor data are processed by the ESP32 microcontroller and conveyed through vibration and audio feedback. The research method includes hardware design, software development, and system testing covering sensor accuracy and response time evaluation. The test results indicate that the proposed system achieved obstacle detection with sensor error rates ranging from 0.2% to 0.6% and response times ranging from 0.7 s to 1.2 s, demonstrating reliable performance for mobility assistance. Therefore, the proposed smart cane has the potential to improve safety and independence for people with visual impairments during walking activities.